2016
DOI: 10.1038/ncomms10291
|View full text |Cite
|
Sign up to set email alerts
|

Chromatin topology is coupled to Polycomb group protein subnuclear organization

Abstract: The genomes of metazoa are organized at multiple scales. Many proteins that regulate genome architecture, including Polycomb group (PcG) proteins, form subnuclear structures. Deciphering mechanistic links between protein organization and chromatin architecture requires precise description and mechanistic perturbations of both. Using super-resolution microscopy, here we show that PcG proteins are organized into hundreds of nanoscale protein clusters. We manipulated PcG clusters by disrupting the polymerization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
231
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(245 citation statements)
references
References 68 publications
14
231
0
Order By: Relevance
“…MBT domains are able to recognize and bind mono-and dimethylated histones [40]. Several studies showed that SAM domain interactions play a crucial role in PcG targeting and clustering, mediate long-range chromatin interactions and affect nuclear organization of repressive centers, called PcG bodies [78] (reviewed in [79]). SAM domain containing subunits of PRCs are prevalent in mammals as well (e.g., SFMBT2, PHC1, PHC2, PHC3, SCMH1 and SCML2), thus polymerization of the SAM domain seems an important feature of PRC mediated silencing.…”
Section: Evolutionarily Conserved Domains In Pcg Proteinsmentioning
confidence: 99%
“…MBT domains are able to recognize and bind mono-and dimethylated histones [40]. Several studies showed that SAM domain interactions play a crucial role in PcG targeting and clustering, mediate long-range chromatin interactions and affect nuclear organization of repressive centers, called PcG bodies [78] (reviewed in [79]). SAM domain containing subunits of PRCs are prevalent in mammals as well (e.g., SFMBT2, PHC1, PHC2, PHC3, SCMH1 and SCML2), thus polymerization of the SAM domain seems an important feature of PRC mediated silencing.…”
Section: Evolutionarily Conserved Domains In Pcg Proteinsmentioning
confidence: 99%
“…For instance, transcriptionally active regions are often co-localised in super-enhancer hubs [8] or transcription factories [14], whereas transcriptionally inactive regions may form large heterochromatic foci [15], mega-base (Mbp) size lamin-associated domains [16] or Barr [17] and Polycomb bodies [18].…”
Section: Introductionmentioning
confidence: 99%
“…16 However, the existence of regular higher order nucleosome structures in vivo has not 17 been demonstrated under physiological conditions. To date, little direct information is 18 available about the functionally crucial 3D folding and structure of chromatin between 19 the scale of single nucleosomes (approximately 5 nm) and the diffraction limit of light 20 (200 nm), which can only resolve entire chromosome territories with a size of a few µm. 21 22 In situ, classically two general types of higher order chromatin organization have been 23 distinguished at a coarser level, euchromatin which tends to be less compact and displays 24 high gene density and activity, and heterochromatin, with a higher degree of compaction 25 and lower gene density and activity [5].…”
mentioning
confidence: 99%